80.4k views
4 votes
Find the value of x when 6 - 4x = 7x-9x - 6 The value of x is​

User Sup
by
5.2k points

1 Answer

4 votes

Answer:

x = 6

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Explanation:

Step 1: Define Equation

6 - 4x = 7x - 9x - 6

Step 2: Solve for x

  1. Combine like terms: 6 - 4x = -2x - 6
  2. Add 4x on both sides: 6 = 2x - 6
  3. Add 6 on both sides: 12 = 2x
  4. Divide 2 on both sides: 6 = x
  5. Rewrite: x = 6

Step 3: Check

Plug in x into the original equation to verify it's a solution.

  1. Substitute in x: 6 - 4(6) = 7(6) - 9(6) - 6
  2. Multiply: 6 - 24 = 42 - 54 - 6
  3. Subtract: -18 = -12 - 6
  4. Subtract: -18 = -18

Here we see that -18 does indeed equal -18.

∴ x = 6 is the solution to the equation.

User GooseSerbus
by
5.8k points